2010
DOI: 10.1016/j.freeradbiomed.2010.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Transport rather than diffusion-dependent route for nitric oxide gas activity in alveolar epithelium

Abstract: The pathway by which inhaled NO gas enters pulmonary alveolar epithelial cells has not been directly tested. Although the expected mechanism is diffusion, another route is the formation of Snitroso-L-cysteine, which then enters the cell through the L-type amino acid transporter(LAT). To determine if NO gas also enters alveolar epithelium this way, we exposed alveolar epithelial-rat type I, type II, L2, R3/1, and human A549-cells to NO gas at air liquid interface in the presence of L-and D-cysteine ± LAT compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…We found that both SNAP and GSNO dramatically inhibited IL-1β secretion in a dose-dependent manner (Figure 1A and Supplementary information, Figure S1A). As L-cysteine facilitates the generation of NO from SNAP or GSNO 24 , the inhibitory effects of these NO donors on IL-1β secretion were greatly enhanced in the presence of L-cysteine. In contrast, the secretion of IL-6 or TNF-α, which depends on Toll-like receptor (TLR) signaling only, was not affected by the presence of these NO donors (Figure 1A and Supplementary information, Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…We found that both SNAP and GSNO dramatically inhibited IL-1β secretion in a dose-dependent manner (Figure 1A and Supplementary information, Figure S1A). As L-cysteine facilitates the generation of NO from SNAP or GSNO 24 , the inhibitory effects of these NO donors on IL-1β secretion were greatly enhanced in the presence of L-cysteine. In contrast, the secretion of IL-6 or TNF-α, which depends on Toll-like receptor (TLR) signaling only, was not affected by the presence of these NO donors (Figure 1A and Supplementary information, Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the biological activity of NO and S-nitrosothiols is not limited to only protection against ischemia-reperfusion injury. S-nitrosothiol formation after inhaled NO administration has recently been proposed as a mechanism of NO delivery to the alveolar epithelium (3), and others have suggested that NO metabolites such as S-nitrosothiols, rather than free NO, mediate some of the beneficial vascular effects of inhaled NO (15).…”
mentioning
confidence: 99%
“…However, it is now understood that NO is a free radical that can be inactivated through interaction with reactive oxygen species found in the alveolar space or alveolar lining. Others propose that NO gas gains entry into alveolar epithelium in part by forming a nitrosothiol derivative of cysteine that enters via an amino acid transporter [76]. Once in the blood stream, NO binds avidly to hemoglobin, which is subsequently reduced by methemoglobin reductase.…”
Section: Pharmacotherapy Of Pulmonary Hypertensionmentioning
confidence: 99%